Microbial inoculants on three medicinal plants of the lamiaceae, colonized with arbascular mycorrhizal fungus. - Gabriel, KP; Yeasmin, T; Lakshman, HC (Journal of Bio-Science, 2019)
Abstract not available J. bio-sci. 26: 01-07, 2018